1996
DOI: 10.1176/ajp.153.10.1329
|View full text |Cite
|
Sign up to set email alerts
|

Structured interview data on 35 cases of dissociative identity disorder in Turkey

Abstract: Dissociative identity disorder has a stable, consistent set of features throughout North America, in the Netherlands, and in Turkey. Cross-cultural research using standardized assessment measures will be invaluable in further illumination of the validity of this widely neglected psychiatric category.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…The change in Rorschach responses of this patient is in accordance with impaired impulsiveness after treatment. Interestingly, in a comparison of Turkish and Dutch patients with DID, large differences existed between the two groups in BPD diagnostic criteria met rather than the core dissociative symptoms (Şar et al, 1996). Namely, Turkish patients reported intense anger and lack of control of this emotion, chronic feelings of emptiness and boredom, efforts to avoid abandonment, and intense but unstable relationships more frequently than Dutch patients.…”
Section: Cultural Preponderance Of Universal Patterns: Extratensitivimentioning
confidence: 99%
“…The change in Rorschach responses of this patient is in accordance with impaired impulsiveness after treatment. Interestingly, in a comparison of Turkish and Dutch patients with DID, large differences existed between the two groups in BPD diagnostic criteria met rather than the core dissociative symptoms (Şar et al, 1996). Namely, Turkish patients reported intense anger and lack of control of this emotion, chronic feelings of emptiness and boredom, efforts to avoid abandonment, and intense but unstable relationships more frequently than Dutch patients.…”
Section: Cultural Preponderance Of Universal Patterns: Extratensitivimentioning
confidence: 99%
“…By using corroborating documentation from hospital, police, and child protection agencies or witnesses, several studies have confirmed histories of severe abuse in DID 29,34,35. In most clinical series, childhood abuse and/or neglect is reported by 90–100% of the patients directly during the study examination 36,37. Dissociative amnesia for childhood events may prevent such reports by some of the patients 38…”
Section: Developmental Traumatizationmentioning
confidence: 98%
“…As a possible example of the influence of culture as a modifier of the expression of DID, in a comparison of Turkish and Dutch patients with DID, large differences existed between the two groups in meeting borderline personality disorder criteria 27,36. Namely, Turkish patients reported intense anger and lack of control of this emotion, chronic feelings of emptiness and boredom, efforts to avoid abandonment, and intense but unstable relationships more frequently than Dutch patients.…”
Section: Family Society and Culturementioning
confidence: 99%
“…Experiencing psychosis symptoms is not necessarily equivalent to having a psychotic disorder. Indeed, though VH is typically considered a psychotic symptom, VH occurs in many nonpsychotic conditions [e.g., mood (4,5), trauma-related (6)(7)(8)(9)(10), personality (11,12), substance-related, and neurological (13)(14)(15) disorders], as well as in 'healthy' individuals (16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%